Borderblur poetics : intermedia and avant-gardism in Canada, 1963-1988 - Schmaltz, Eric, 1988- (University of Calgary Press, 2023)
"Discover how avant-garde artists challenged the cultural hegemony with intermedial forms of literary production in this exciting examination of Canada's borderblur poets. Beginning in 1963 and continuing through the late 1980s, a loose coterie of like-minded Canadian poets challenged the conventions of writing and poetic meaning by fusing their practice with strategies from visual art, sound art, sculpture, instillation, and performance. They called it "borderblur" Borderblur Poetics traces the emergence and proliferation of this node of poetic activity, an avant-garde movement comprising concrete poetry, sound poetry, and kinetic poetry, practiced by poets and artists like bpNichol, bill bissett, Judith Copithorne, Steve McCaffery, Penn Kemp, Ann Rosenberg, Gerry Shikatani, Shaunt Basmajian, among others. Author Eric Schmaltz demonstrates how these poets formed an alternative tradition, one that embraced intermediality to challenge the hegemony of Canadian literature established during the heydays of cultural nationalism. He shows the importance of intermediality as a driving cultural force and how its proliferation significantly altered Canadian cultural expression. Drawing on a combination of archival research, historical analysis, and literary criticism, Borderblur Poetics adds significant nuance to theories and criticisms of Canadian literature."--